Adoption of Social Media in Investment Decision At Stock Market: A Qualitative Analysis Among Nepali Investors - Pandit, Kulchandra; Vaidya , Rashesh (Journal of Balkumari College, 2022)
The importance of social media has increased among investors due to the instant availability of information on a real-time basis. The adoption of social media even increased heavily during the COVID-19 pandemic. The reliability of the posts related to the stock market is the concern; nevertheless, follow them to track the stock market trend. The Nepalese stock market investors found to follow the posts, opinions, and views on social media but are reluctant to follow blindly. Similarly, the Nepalese investors have partial faith in the specialized group formed on social media, and found to be attached to the group to get information. But the investors filter the information as per their knowledge and necessity.